Fiscality as Expression of the Type of State (Papeles, 2020)
In the midst of the pandemic, and in the face of future uncertainties, the Medium-Term Fiscal Framework, prepared by the Ministry of Finance for the period 2021-2031, shows that the crisis has not led the government to rethink the type of State. Colombia would continue with a very weak public intervention. In addition to showing the inconvenience of continuing with a rickety State, the article questions the projection model based on stationary equilibrium. Based on this narrow logic, it is concluded, wrongly, that the immediate growth of the Colombian economy will be in the form of V.
Keywords: stationary equilibrium; State; economic growth